2009
DOI: 10.1111/j.1558-5646.2009.00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Components of Reproductive Isolation Between North American Pheromone Strains of the European Corn Borer

Abstract: Of 12 potential reproductive isolating barriers between closely related Z-and E-pheromone strains of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
212
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(218 citation statements)
references
References 123 publications
4
212
2
Order By: Relevance
“…First, multiple 'speciation phenotypes' (Shaw and Mullen, 2011) in ECB have known sex-linked factors, including male pheromone response and diapause timing (McLeod, 1978;Dopman et al, 2004;Wanner et al, 2010;Ikten et al, 2011). Second, a recent study indicated that large isolation effect sizes are common between ECB strains (RI ⩾ 0.5 for 4 of 7 forms of isolation; Dopman et al, 2010). Given this prior work and the large size of the putative inversion (7 cM or~4 Mb; Figure 2b), there would appear to be good reason to expect diverse and potent barrier loci in an inversion on the ECB sex chromosome.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…First, multiple 'speciation phenotypes' (Shaw and Mullen, 2011) in ECB have known sex-linked factors, including male pheromone response and diapause timing (McLeod, 1978;Dopman et al, 2004;Wanner et al, 2010;Ikten et al, 2011). Second, a recent study indicated that large isolation effect sizes are common between ECB strains (RI ⩾ 0.5 for 4 of 7 forms of isolation; Dopman et al, 2010). Given this prior work and the large size of the putative inversion (7 cM or~4 Mb; Figure 2b), there would appear to be good reason to expect diverse and potent barrier loci in an inversion on the ECB sex chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Differences at Pdd contribute to temporal isolation between Z and E strains in North America by conferring an~30-day shift in emergence and thus adult-mating flights (Wadsworth et al, 2013). Shifts in adult flights between univoltine Z and bivoltine E populations eliminate as much as 85% gene flow in nature (Dopman et al, 2010).…”
Section: Colocalization Of Reproductive Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…The first set is sex-linked, as often in lepidopteran incipient species (Prowell, 1998). It includes genes affecting post-diapause development time (Pdd: Glover et al, 1992;Dopman et al, 2005Dopman et al, , 2010, male behavioural response to different female sex pheromones (Resp: Glover et al, 1990;Dopman et al, 2004Dopman et al, , 2005Dopman et al, , 2010, differential success rate in larval development on either host plant (Calcagno et al, 2007) and/or other genes located in the vicinity of Tpi (Bourguet et al, 2000;Martel et al, 2003;Bontemps et al, 2004;Dopman et al, 2004Dopman et al, , 2005. The second set of candidates is autosomal and includes genes responsible for differences in female sex pheromones (Pher: Roelofs et al, 1987;Dopman et al, 2004Dopman et al, , 2010Lassance et al, 2010), an unidentified close-range mechanism ensuring assortative mating in laboratory settings (AssMat: Pélozuelo et al, 2007) and/or other genes located in the vicinity of Mpi (Bourguet et al, 2000;Martel et al, 2003;Bontemps et al, 2004).…”
Section: Discussionmentioning
confidence: 99%